Pengaruh Jenis dan KonsentrasiFillerterhadap Karakteristik Bioplastik Berbahan BakuPati Singkong - Alwin Sihombing; Ni Luh Yulianti; Ida Bagus Putu Gunadnya (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2024)
The physical characteristics of bioplastic packaging can be affected by the type and concentration of filler. This research was conducted to obtain bioplastic packaging films that met the Indonesian National Standard (SNI). The experimental design used was a randomized block design (RBD) with the first factor being the type of filler (J) with 2 levels: ZnO and cellulose. The second factor is the concentration of filler (K) with 3 levels, namely 0.5; 0.7; 0.9g. Each treatment was repeated three times, so the re were a total of 18 experimental units. The data will be analyzed using variance. If it turns out that the treatment has a significant effect on the parameters being observed, then the next step is to perform Duncan's test. The results indicated that the different types and concentrations of filler in the manufacture of bioplastic packaging had an effect on the values of tensile strength, elongation, elasticity, water absorption but had no effect on the rate of bioplastic biodegradation. Treatment with cellulose filler concentration of 0.5 g was the treatment that produced bioplastic packaging with the best characteristics, namely tensile strength of 14.31 MPa, elongation of 24.76%, elasticity of 53.72 MPa, water absorption of 0.71% and long biodegradati on time 7.5 days.